Ontogeny and modulation after PAMPs stimulation of β-defensin, hepcidin, and piscidin antimicrobial peptides in meagre (Argyrosomus regius). Issue 69 (October 2017) - Campoverde, Cindy; Milne, Douglas J.; Estévez, Alicia; Duncan, Neil; Secombes, Christopher J.; Andree, Karl B.
Abstract: Antimicrobial peptides (AMPs), components of innate immunity, play an important role in protecting fish. In this study we report the molecular cloning of full open reading frames and characterization of expression of three AMP genes ( β-defensin ( defb ), hepcidin ( hep2 ), piscidin ( pisc ) in meagre ( Argyrosomus regius ). A phylogenetic analysis of the expressed sequences obtained shows the defensin isoform forms a clade with the other members of the beta class of this family, hepcidin corresponds to hepcidin 2, and piscidin corresponds to class I of its respective family. Gene expression profiles of AMPs was investigated, by means of quantification of mRNA in nine development stages, from 8 days post-hatching (dph) to accomplishment of juvenile form (120 dph). During development it was demonstrated defb, hep2, pisc were expressed in all stages of larval development and in juvenile tissues (kidney, spleen gut and gill). Moreover, expression patterns suggest the expression levels of theses AMPs are influenced by live prey (rotifer, Artemia ) and first intake of commercial diet. Induction experiments in vivo (24 h) and in vitro (4, 12, 24 h) with PAMPs (LPS, poly (I:C), β-glucan) revealed significant changes in gene expression of the three AMP genes, in kidney, spleen, gut and gill. However, expression profiles differed in magnitude and time course response. defb expression shows a similar trend in vivo and in vitro in kidney at 24 h after LPS and β-glucan stimulation. The hep2 expression levels were up-regulated upon β-glucan challenge in vivo, more in gut and gills than kidney, while in vitro hep2 expression was up-regulated in kidney cells by LPS, poly (I:C), β-glucan (4 h). pisc expression was up-regulated in kidney cells, splenocytes by β-glucan, but in gill cells by poly (I:C) and β-glucan in vivo . However, pisc expression was upregulated in kidney cells by β-glucan and gill cells by LPS at 4 post-stimulation in vitro . These data suggest that AMPs play an important role in defense against pathogens, with each AMP having differing efficacies against specific types of microorganisms, although follow-up studies focusing on the biological activities in fish are needed. Highlights: First report of antimicrobial peptide (AMPs) transcripts in meagre, Argyrosomus regius. β-defensin, hepcidin, and piscidin, AMPs transcripts were expressed in different level in early developmental stages. AMPs expression from meagre likely influenced by dietary factors. AMPs expression was modulated in response to PAMPs in a tissue-specific manner.